Pengaruh Kualitas Produk Gula Merah Ampera Terhadap Keputusan Pembelian Konsumen Di Kecamatan Pagimana: Effect Of The Quality Of Ampera Brown Sugar Products On Consumer Purchasing Decisions In Pagimana Subdistrict - Liswan Rusman; Yusnita Fitarini Sibay; Heny Ariwijaya (Jurnal Ilmiah Produktif, 2021)
This study aims to find out how the quality of Ampera brown sugar products affects consumer purchasing decisions in the pagimana subdistrict. The number of respondents in this study was 50 respondents. The analyses used in this study are simple linear regression, correlation coefficient, determination coefficient, and t-test. Results using a simple linear analysis of Y = 1.302 +0.717X give the meaning that what if the quality of the product or independent variable (free) has a value of 0 (zero) or none. So the variable value of the purchase decision is 1,302. The analysis results using the t-test can be found that the quality of the product has a significant effect on purchasing decisions. The contribution or contribution of product quality of 0.371 or 37.1% while other variables influence the remaining 63%, and the result of the correlation relationship of 0.609 or 60.9% belongs to the strong category, so there can be a strong relationship between product quality and Ampera brown sugar purchase decisions in Pagimana Subdistrict.